2011
DOI: 10.7326/0003-4819-154-7-201104050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Effect of Patient Self-testing and Self-management of Long-Term Anticoagulation on Major Clinical Outcomes

Abstract: U.S. Department of Veterans Affairs Health Services Research and Development Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 60 publications
10
134
0
Order By: Relevance
“…Our findings are in line with those of previously published systematic reviews on self-monitoring using point-of-care devices for the management of anticoagulation therapy, which found that self-monitoring was associated with a significantly lower incidence of thromboembolic events 21,31,33,88,108,[135][136][137] and deaths. 21 …”
Section: Chapter 4 Discussionsupporting
confidence: 82%
“…Our findings are in line with those of previously published systematic reviews on self-monitoring using point-of-care devices for the management of anticoagulation therapy, which found that self-monitoring was associated with a significantly lower incidence of thromboembolic events 21,31,33,88,108,[135][136][137] and deaths. 21 …”
Section: Chapter 4 Discussionsupporting
confidence: 82%
“…Clinical scores-eg, the HEMORR2HAGES score 69 and the RIETE score 70 (table 4) interactions, restriction of alcohol ingestion, and, in some patients, with use of self-monitoring or even selfmanagement, 71 which remains debated. 72,73 Additionally, large loading doses should be avoided to prevent development of a paradoxical prothrombotic state due to the depletion of protein C, a vitamin K-dependent coagulation inhibitor with a very short half-life. Whether rapid turnaround genetic testing will be clinically useful to guide warfarin dosing remains to be established.…”
Section: Safety Of Anticoagulant Treatmentmentioning
confidence: 99%
“…Finally, selftesting of international normalized ratio is feasible, well accepted, and cost-effective. 6 Therefore, we are slow to recommend these newer, more expensive anticoagulant agents. After the publication of our report, we have become aware of postmarketing cases of DILI from rivaroxaban.…”
Section: Use Of Nontraditional Anticoagulants In Portal Vein Thrombosmentioning
confidence: 99%